Monitoring and Evaluating Adaptation Investments Opportunities for the Private Sector - Isbell, Carina; Jones, Kristal; Nowak, Andreea C.; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Key messages There is an urgent need for private sector finance for adaptation, yet there is a lack of adequate tools to ramp up investments. • Monitoring and evaluation (M&E) can help to track adaptation benefits and build the case for increased finance. • M&E information can also strengthen accountability and transparency, build supply chain resilience, and meet demands from climate-conscious supply chain actors. • Alignment between adaptation indicators and impact investing reporting systems provides an important starting point for enhancing M&E of adaptation investments.